Analysis of Indonesian Public Service Issues in The New Era based on Public Administration Perspective - Arip Rahman Sudrajat (International Journal of Social Service and Research (IJSSR), 2023)
Public trust is an important variable in improving public services. However, the existence of unhealthy protests and demonstrations indicates the current bad public services. This study aims to analyze the issue of public services in Indonesia in a new era from an administrative perspective. The research method used in writing this scientific article is to use the method of literature study (library research) using qualitative and descriptive analysis. The New Public Service and Good Governance perspective is considered the most appropriate to answer the current condition of public service problems in Indonesia. This is supported by a more democratic political situation and open government. To effectively implement this point of view, it can be implemented using various models such as the Citizen Charter model, the KYC (Know Your Customer) model, and the Mobile Government model.